IMPLIKASI STRATEGI PEMASARAN MELALUI KOMODIFIKASI AGAMA - HERLINA YUSTATI (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2017)
Religion in Indonesia is divided into Muslim, Christian, Catholic, Hindu, Buddhist,Khong Hu Chu and Other Religions. Religion Islam is the majority religion embracedby the Indonesian population, so that business people use this opportunity to recommodificationof religion. Commodification describes how capitalism launched anaim to accumulate capital, or realize the transformation of use-value into exchangevalue. The commodification of Islam in Indonesia occurred in various aspects. Mislanyacommodification "sharia" through aspects of banking, insurance, hotel, tourism, etc.The commodification of Islamic symbols such as headscarves and halal labeling.Besides being able to be used as a marketing strategy for businesses, komodiikasi Islamalso bring positive things if businesses make this situation as a means of education. Theimpact of the commodification of Islam such as the increasing development of Islamicfinancial institutions in Indonesia, increased public awareness to abandon usury,increased public awareness using the "sharia", the increasing number of Muslimwomen who wear the hijab and the increasing awareness of Muslims to use halalproducts not only in food but also in cosmetics.